Effect of graphene incorporation in carbon nanofiber decorated with TiO2 for photoanode applications. Issue 11 (20th January 2017) - Lee, Hoik; Nagaishi, Tomoki; Phan, Duy-Nam; Kim, Myungwoong; Zhang, Ke-Qin; Wei, Kai; Kim, Ick Soo
Abstract : The photovoltaic performance of dye-sensitized solar cells (DSSCs) using a photoanode fabricated with graphene incorporated carbon nanofibers with a TiO2 layer on their surfaces is reported. Abstract : The photovoltaic performance of dye-sensitized solar cells (DSSCs) using a photoanode fabricated with graphene incorporated carbon nanofibers with a TiO2 layer on their surfaces is reported. The composite nanofibers were prepared through a process consisting of electrospinning and sol–gel process. The distribution of TiO2 particles on the surface of the graphene-incorporated carbon nanofiber was characterized by scanning electron microscopy (SEM), and transmission electron microscopy (TEM). From the microscopic studies, we found that graphene plays a significant role to form TiO2 particles on carbonaceous materials. Further studies on chemical composition using X-ray photoelectron spectroscopy reveal that different oxidation states of Ti in the synthesized titanium oxide were achieved by incorporating graphene in the nanofibers. Furthermore, TiO2 synthetic conditions in the sol–gel process largely affected photovoltaic performance, particularly short circuit current; acidic conditions for the sol–gel process were more effective compared to neutral conditions. The incorporated graphene facilitates conducting charge carriers in TiO2 by coordination with carbon, and increasing the adsorption of dye molecules owing to homogeneous distribution of TiO2 along the nanofibers. This study further highlights the advantages of hybridizing different materials with 1D nanofiber geometry, offering a promising route to improving the resulting efficiency in light harvesting applications.